2004
DOI: 10.1002/jcb.20110
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β1 enhances βig‐h3‐mediated keratinocyte cell migration through the α3β1 integrin and PI3K

Abstract: betaig-h3 is an extracellular matrix (ECM) protein whose expression is highly induced by transforming growth factor beta1 (TGF-beta1). We previously demonstrated that betaig-h3 has two alpha3beta1 integrin-interacting motifs, which promote adhesion, migration, and proliferation of human keratinocytes. Both betaig-h3 and TGF-beta1 have been suggested to play important roles in the healing of skin wounds. In this study, we demonstrate that TGF-beta1 enhances keratinocyte adhesion and migration toward betaig-h3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 34 publications
4
55
0
Order By: Relevance
“…Low levels of activated Akt are observed in human RCC cells (20). Some important factors, including EGF, VEGF, and TGF-b, are involved in the tumorigenesis of human carcinoma through activation of PI3K/Akt signaling cascade (38)(39)(40). These growth factors derived from RCC may be responsible for the constitutive activation of Akt.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of activated Akt are observed in human RCC cells (20). Some important factors, including EGF, VEGF, and TGF-b, are involved in the tumorigenesis of human carcinoma through activation of PI3K/Akt signaling cascade (38)(39)(40). These growth factors derived from RCC may be responsible for the constitutive activation of Akt.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TGF-␤ stimulation of FAK 397 enhances migration in keratinocytes and hepatocarcinoma cells. 74,75 TGF-␤-induced fibroblast differentiation to myoblasts was shown to require adhesiondependent FAK activation by some investigators, 73 although others have suggested that in some cases FAK effects on differentiation may be mediated by interactions with another growth factor. 76 Finally, TGF-␤ acts synergistically with integrins to activate FAK and induce phenotypic changes in rat podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…TGFBI protein contains a signal peptide in the first 24 amino acid residues at the N-terminus, a cysteine-rich EMI domain, four highly conserved fasciclin (FAS) domains and several integrin-binding motifs including the RGD motif in the C-terminus, which serves as a ligand-recognition site for several integrins (LeBaron et al 1995, Ohno et al 1999, Bae et al 2002, Jeong & Kim 2004, Kim & Kim 2008. Other integrin-binding motifs include the NKDIL motif (amino acids 354-358) (Kim et al 2000), the EPDIM motif (amino acids 617-621) (Kim et al 2000) in the second and fourth FAS-1 domains, respectively, and the YH18 motif (amino acids 563-580) in the fourth FAS-1 domain, which can support αvβ5 integrin-mediated adhesion of lung fibroblast MRC-5 cells , vascular smooth muscle cells (Lee et al 2006) and endothelial cells (Nam et al 2003).…”
Section: Role Of Tgfbi In Ovarian Cancermentioning
confidence: 99%
“…Effects of TGFBI on adhesion are mediated through interactions with various integrins including α1β1, α3β1, αvβ3 and αvβ5 (LeBaron et al 1995, Ohno et al 1999, Bae et al 2002, Jeong & Kim 2004, Kim & Kim 2008) via the different integrin-binding motifs. TGFBI also functions as a linker protein and connects many matrix proteins including collagens (type I, II and IV), fibronectin (Billings et al 2002) and proteoglycans (biglycan and decorin) with each other (Gibson et al 1997, Billings et al 2002, Hanssen et al 2003, Reinboth et al 2006.…”
Section: Role Of Tgfbi In Ovarian Cancermentioning
confidence: 99%